EFEK KONDISI PERTUMBUHAN TERHADAP PRODUKSI -GLUKAN OLEH EPICOCCUM NIGRUM SECARA KULTUR BATCH DALAM CONTINUOUSLY STIRRED TANK REACTOR (CSTR) - . Jayus; Sony Suwasono; . Giyarto (JURNAL AGROTEKNOLOGI, 2007)
Batch culture fermentation in CSTR system was operated under different agitation speeds and aeration rates in attempt to optimize production of -glucan from Epicoccum nigrum. It was found that its production was influenced by both of the agitation speed and aeration rate. However, the yields obtained were lower compared to that in shake flask culture, indicating that E. nigrum is sensitive to agitation speed and aeration rate. Keywords: E. nigrum, -glucan, batch culture fermentation in CSTR